Anomalous origin of the left vertebral artery from the arch of the aorta - Jasiewicz, Maria; Sajdak, Piotr; Sopel, Aleksandra; Strzępek, Kamil; Ziajor, Seweryn; Pliszka, Anna; Balawender, Krzysztof (European Journal of Clinical and Experimental Medicine, 2021)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Although there are lots of varieties of aorta arch, they seem to appear relatively rarely. Anomalies of aortic arch departures are mainly concerned with its location, course, the place of departure and number of its main branches. However, they warrant attention due to their importance in operative, diagnostic, and endovascular procedures. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. We want to present here a case of a female cadaver with rare aortic arch origin of the left vertebral artery. The aim of this article is to complete the frame of anomalies in aortic arch and to explore rare variability shown in this specific case. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. The present report describes an anomalous case of the left vertebral artery arising from the aortic arch between the left common carotid artery and the left subclavian artery in a female cadaver during dissection in an anatomical laboratory. Aortic origin of the vertebral artery is a rare anatomic variant. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Thorough knowledge of anomalous origin is important for patients who undergo operation of an aortic arch or inferior part of the neck. Normally, the vertebral artery arises from the first part of the subclavian artery on both sides.